Activity-Based Protein Profiling Delivers Selective Drug Candidate ABX-1431, a Monoacylglycerol Lipase Inhibitor, To Control Lipid Metabolism in Neurological Disorders - Jiang, Ming (J Med Chem, 2018)
Monoacylglycerol lipase (MGLL or MAGL) is a critical point of regulation of both endocannabinoid and eicosanoid signaling pathways in the brain, thereby providing novel therapeutic opportunities for neurological and neurodegenerative diseases. In this issue Cisar et al. disclose the discovery, optimization, and initial preclinical profiling of ABX-1431, a covalent, irreversible MGLL inhibitor. Activity-based protein profiling was key to the discovery of ABX-1431. ABX-1431 is a first-in-class experimental drug that was well-tolerated and safe in phase 1 clinical studies. Data from an exploratory phase 1b study indicate that it has the potential to treat symptoms of adult patients with syndrome of Gilles de la Tourette. ABX-1431 is currently entering clinical phase 2 studies for this neurological disorder as well as for other indications, such as neuromyeltis optica and multiple sclerosis.